2014
DOI: 10.1017/s1751731113002000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for feed intake, litter weight, body condition and rebreeding success in primiparous Norwegian Landrace sows

Abstract: The aim of this study was to estimate genetic parameters for feed intake recorded as farmers' perception of young sows' appetite for the first 3 weeks of lactation (APP) and feed intake recorded for one day in the 3rd week of lactation (FEED), litter weight (LW) at 3 weeks, sow body condition at weaning (BC) and the following five reproduction traits: weaning-to-service interval of 1 to 7 days (WSI7), weaning-to-service interval of 1 to 50 days (WSI50), delayed service or not (DELAYED), pregnant on first servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…,Rydhmer et al (2008),Su et al (2008),Wallenbeck et al (2008),Clapperton et al (2009),Davies et al (2009), Nejsum et al (2009,Canario et al (2010),Gourdine et al (2010),Lundgren et al (2010Lundgren et al ( , 2012Lundgren et al ( , 2014 b See…”
mentioning
confidence: 99%
“…,Rydhmer et al (2008),Su et al (2008),Wallenbeck et al (2008),Clapperton et al (2009),Davies et al (2009), Nejsum et al (2009,Canario et al (2010),Gourdine et al (2010),Lundgren et al (2010Lundgren et al ( , 2012Lundgren et al ( , 2014 b See…”
mentioning
confidence: 99%
“…Heritability estimate for this trait was low: 0.04 for LY and 0.12 for LL. Also in different studies reported before, heritability for WCI tended to be low [1,2,8]. The heritability for WCI after first parity was higher than after second parity [12].…”
Section: Discussionmentioning
confidence: 93%
“…Lundgren et al [8] observed that sows with genetic capacity for a high body condition at weaning may produce more piglets in the second parity, which suggests that it is reasonable to focus more attention on the LL and LY sow body condition before and after weaning of piglets and to measure these values.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, GS has been reported to be more suitable than REML analyses for the analysis of complicated models, as it can obtain and update all information from the posterior probability distribution without solving the mixed model equations (Gianola and Fernando, 1986;Van Tassell et al, 1995). Therefore, the GS method is increasingly used to estimate the genetic parameters of quantitative traits (Waldmann and Ericsson, 2006;Pardo et al, 2013), such as BW in cattle (Lundgren et al, 2014), feed intake and litter weight in sows (Lopes et al, 2013), and egg production in chicken (Luo et al, 2007). In this study, a comparison of the estimates obtained using the REML and GS methods were determined to be similar; this was consistent with the results obtained in other studies (Van Tassell and Van Vleck, 1996;Andersen-Ranberg et al, 2005;Stock et al, 2007).…”
Section: Discussionmentioning
confidence: 99%